Ovarian dermoid cysts - Espinoza Ramirez, Alberto (2015)
At present this work for consideration by the Second Peruvian Congress of Gynecology and Obstetrics, I thought it necessary to review the knowledge on the dermoid cyst, are now in the light of modern study on the embryology of the ovary. The statistic that I present has been collected in the archives of the Pavilion 5, Room 1a. Archbishop Loayza Hospital, during the 1951-1960 decade.